VISION, MISSION AND TRANSMISSION - Ouseparampil (Journal of Dharma, 1981)
India has been described as the land of l;is (seers). We have in our land, from time immemorial, ascetics who experienced ecstacy through meditation, silence and asceticism. They were also observers of rigorous vows. They were known by various names, related to their style of life. Thus some of them were called Vrãtyãs wandering mendicants, Yatis - practising penance as against r.§is who were householder — sages of the Vedic times. We confine our studies mainly to the (§is of IRg Veda and Atharva Veda. In these sources they are called by different names such as kavi, manï§i etc. Kavi is a poet and manï§i is a saint. " Kavirmanï§i paribhuh, defines Išäväsya upanishad 8. Šañkara commented on it saying kaviþ krantadarsi sarvadrk - Kaviþ is one who sees the Reality through the fleeting appearances and he has the cosmic vision. Manïsi is manasai§ita sarvajña îšvaraþ: manï§i has omniscience and lordly power.